Survey of Volunteer Activity, 1987 [Canada]: Organization File - Statistics Canada. Special Surveys Group (Borealis, 1990)
The Survey of Volunteer Activity (VAS) was undertaken by Statistics Canada to profile the characteristics of individual volunteers. This survey provides previously unavailable information regarding the activities of volunteers, the organizational settings in which these activities take place, reasons for becoming volunteers, the amount and pattern of time spent on these activities, the cost of volunteering as well as personal opinions on aspects of voluntary experience. The Organization File contains information for the organizations reported by formal volunteers as well as personal characteristics and summary variables from the volunteer file. This file was created to simplify tabulation in studies where the organization, rather than the person, is to be the unit of analysis. The Survey of Volunteer Activity was conducted as a supplement to Statistics Canadas November 1987 Labour Force Survey (LFS). Coverage includes all Canadian individuals aged 15 and over excluding residents of the Yukon and Northwest Territories, inmates of institutions, full-time members of the Canadian Armed Forces and residents of Indian reserves.